The potential use of light pipe system as illumination element for one storey building in Malaysia - Abd. Kadir, Aslila (2022)
Daylighting is an efficient and practical strategy for illuminating the interiors of buildings with natural light during the day. Natural light is extremely beneficial for energy conservation, the occupants' health and psychological well-being, and the environment. Light pipe system (LPS) is a lighting device that can capture sunlight from the rooftop and transmits into the low light area or into rooms with insufficient daylight. The purpose of this study was to determine the potential of a light pipe system for interior illumination in single storey building spaces in Malaysia. The physical experiment was conducted in a test room to determine the light pipe system's overall potential. Meanwhile, a computer simulation was used to determine the illuminance distribution of the LPS and artificial lighting in order to calculate energy savings. The simulation was conducted in three scenarios, (1) with one LPS, (2) with two LPS, and (3) with three LPS. The results indicate that the LPS performed admirably under intermediate sky and met the building's minimum illuminance (100 lux) requirements, as recommended by MS 1525:2014. Furthermore, the analysis of the daylight performance results was based on Work Plane Illuminance (WPI), the daylight penetration factor (DPF) and illuminance uniformity. The results illustrated that the LPS performance was reasonable , but the presence of clouds disrupted the capacity of the LPS to achieve the illuminance recommended. As a result, artificial lighting was used as a source of power. By combining a light pipe system with artificial lighting, it is possible to achieve an adequate level of illumination in a room while reducing electricity consumption. The simulation results indicate that using two LPS is more beneficial in a 15 m2 space than using one or three LPS. Using two LPS for the test room with the artificial lighting system and applying the dimming control, the reduction was up to 25 per cent per day, suggesting that 114 kWh could be saved annually. In parallel, the CO2 emissions produced from the energy usage could be reduced to 80 kg per year. Both reductions would contribute to saving to the environment. This discovery provide useful information to building designers intending to implement LPS and this system will be widespread use of LPS in Malaysia.